From Green Marketing to Enhance Green Purchase Intention: The Act of Green Advertisement, Green Brand Loyalty, and Green Brand Innovativeness - Della Ayu Zonna Lia; Ely Siswanto; Rayie Tariaranie Wiraguna; Handri Dian Wahyudi (University of Merdeka Malang, 2024)
The present study aims to investigate the effects of Green Marketing (GM) strategies, such as Green Advertisement (GA), Green Brand Loyalty (GBL), and Green Brand Innovativeness (GBI), on consumer purchase intention. Additionally, it investigates the moderating effects of these strategies on these relationships and looks at how GM and Green Purchase Intention (GPI) are related. These findings build on previous research on the relationship between GM and GPI. The unresearched combined effects of GM on customer purchase intentions as well as the moderating functions of GA, GBL, and GBI in these connections are among the research gaps. The current study examines the relationship between GM antecedents and GPI using a cross-sectional approach and a quantitative research methodology. Quantitative research methods are useful when analyzing relationships between variables and extending findings across populations is the goal. Based on prior research on GM and behavior, the study's research methodology used a survey questionnaire. Google Forms will be used to distribute an online survey to Indonesian consumers of green products, which served as the data collection tool for this study.